2018
DOI: 10.1111/cns.13044
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of white matter and gray matter revealed by diffusion tensor imaging and pathological mechanism after spinal cord injury in canine

Abstract: Diffusion tensor imaging is more sensitive to degeneration of white matter than gray matter, and the white matter degeneration may be not symmetrical which meant the caudal degradation appeared to be more severe than the rostral one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Within the gray matter, the principally cellular microstructure typically has predominant isotropic diffusion characteristics that are best evaluated by apparent diffusion coefficient (ADC) maps . However, multiple studies have shown that FA values, markers of anisotropic diffusion, may also alter the microstructural anatomy if affected by a diffuse process . For example, in patients with a cortical stroke, the FA values may increase within the cortical gray matter, likely secondary to a combination of cytotoxic and vasogenic edema impacting the diffusion of water molecules within the extracellular space .…”
Section: Discussionmentioning
confidence: 99%
“…Within the gray matter, the principally cellular microstructure typically has predominant isotropic diffusion characteristics that are best evaluated by apparent diffusion coefficient (ADC) maps . However, multiple studies have shown that FA values, markers of anisotropic diffusion, may also alter the microstructural anatomy if affected by a diffuse process . For example, in patients with a cortical stroke, the FA values may increase within the cortical gray matter, likely secondary to a combination of cytotoxic and vasogenic edema impacting the diffusion of water molecules within the extracellular space .…”
Section: Discussionmentioning
confidence: 99%
“…And the retention of cerebrospinal fluid (CSF) at the injury site may increase the diffusion degree of water molecules, resulting in the increase of MD value. There are also some studies on acute SCI that indicate a transient decrease in MD value postinjury [ 5 , 46 ], which may be the result of cell swelling, as it can cause an increase in cell radius, leading to an increased tortuosity, and ultimately induce a decrease in MD value [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The software measured the intensity of the brown color—a HRP reaction product. In order to enhance the accuracy of quantification, only the percentage of “high positive” staining intensity was measured [ 43 ].…”
Section: Methodsmentioning
confidence: 99%